Factors Associated with Help Seeking Behavior of Turkish Women with Urinary Incontinence; A Single Center Cross-Sectional Study - Seyhan Sönmez; Ersen Eraydın; Yalçın Arıcan; Ferhan Sönmez (Medical Network, 2017)
Objectives: The aim of this study was to determine the patient and UI-related factors affecting help seeking behavior of Turkish women with undiagnosed urinary incontinence Methods: This cross-sectional study was conducted on 490 female patients aged > 18 years old and were seen in general gynecology outpatients' clinic of Denizli State Hospital. According to referral complaint and results of UDI-6 questionnaire, the participants were classified into 3 groups: Group A: Help seeker patient, Group B: Non help seeker patient and Group C: Continent patient. Results: Overall UI prevelance was 24%. Nearly two thirds ( 67% ) of the UI patients do not complaint about their UI symptoms unless they were asked specifically about UI. Consultation rate increased with age, duration of incontinence, menopause and the severity of UI. After logistic regression analyses, only increasing age, UDI-6 score and severity (SSS) were found to be associated independently with help seeking behavior. Conclusions: This study showed that, older, more bothered and severe UI patients visit physician and seek medical help. Still nearly half of women who are suffering from clinically significant UI remain undiagnosed and untreated. Regardless the visiting reason if its asked specifically for UI symptoms by using simple questionnaires, we can reveal and diagnose this patients' group that is suffering from UI but yet keeps it disguise . Keywords: Urinary incontinence, help seeking behavior, undiagnosed urinary incontinence